Flood Inundation Mapping of Babai Basin using HEC-RAS & GIS - Bhattarai, Pawan; Khanal, Prajwal; Tiwari, Prachanda; Lamichhane, Nischal; Dhakal, Prasanna; Lamichhane, Prakash; Panta, Niranjan Raj; Dahal, Prashant (Journal of the Institute of Engineering, 2019)
The main objective of this research is to prepare inundation map of a section of Babai Basin and to find out the inundated areas for different return periods. In order to achieve the objectives, Geographic Information System (GIS) and HEC-RAS along with HEC-GeoRAS extension were used as tools. Coordinates were used as primary parameter and were obtained from survey to generate geometric data such as Triangular Irregular Networks (TIN), streamline, river bank and flow paths. After importing the geometry data into HEC-RAS, hydraulic modelling was applied by using flow data as main input. As a result, the watershed area of the Babai basin has been successfully modelled and map showing the flooded areas along the Babai basin has been delineated. The flooded area was geometrically overlaid on the topographic map to outline the affected areas. The area under the influence of the flood were assessed which shows that about 49% of total inundated areas comprises farming land. Also a sensitivity analysis was performed to predict the change in percentage of flooded areas when Maning’s parameter was increased by 10% and when kept same in both banks and channel. However, differences in figure of inundated areas are insignificant to variations made in Maning’s n.